The politics of nation building and citizenship in Singapore - Hill, Michael (Politics in Asia series, 1995)
Examines basic concepts of citizenship, nationality and the state in the context of Singapore's independence. The theme of nation-building is explored and how the creation of a national identity, through building new institutions, has been a central feature of life in Singapore.